A-AARNET training course for researchers on breeding strategies for use of animal genetic resources in eastern and central Africa.Workshop material. Facilitated by ILRI - SLU Team. Capacity building for sustainable use of animal genetic resources in developing countries - Bealby, K.A.; Chisanga, H.K.; Silutongwe, J.; Connor, R.J.; Rowlands, G.J. (2006)
The A-AARNET (ASARECA Animal Agriculture Research Network) training course for researchers on breeding strategies was given by Han Jianlin of ILRI Nairobi. The course topics are as follows. Genes, genomes and genomics: an introduction; Cloning, restriction endonuclease and DNA sequencing; Detection of sequence polymorphisms: principles of molecular markers related techniques; Polymerase Chain Reaction (PCR); Sampling animal for genetic analysis; and application of molecular genetic markers in livestock. This was followed by participants' presentation. This includes, Genetic polymorphism and population structure of milk structure of milk protein loci in some Sudanese cattle, sheep and goat breeds; Characterisation of production traits, establishment of genetic potential and improvement of indigenous breeds of sheep and goats in Tanzania; Characterization of production traits, establishment of genetic potential and improvement of indigenous breeds of sheep and goats in East and Central Africa; ONB as a tool to increase goat productivity through improved germplasm, and management practices for sustainable market oriented systems in smallholder farmers; Characterization and searching for fecundity gene in Sudanese sheep breeds; Testing and validation of breed survey methodology, socio-economic survey and characterization of selected indigenous cattle breeds of eastern and central Africa; Introduction of improved animals in Busoni Kirundo Province ; Effects of absorption breeding (Ankole-Sahiwal, Jersey-Sahiwal) on milk production in livestock research centers of ISABU; Crossbreeding Boar goat with indigenous goat breed - a strategy for enhanced goat productivity in Rwanda; Introduction of improved dairy processing technologies to market-oriented smallholder dairy producers in the Ethiopian highlands; Genetic selection of Arsi-Bale goats for increased body weight; Establishment of superior genetic materials through importation of sexed embryo for embryo transfer research at Debre Zeit; Performance evaluation of crossbred dairy on some dairy farms in Rwanda; Improvement of Renitelo cattle breed diffusion - maintenance of cattle breed created by research (PSDR project); Conservation of standard Ankole - Bashi : a way to preserve diversity of Ankole race. A breed survey questionnaire is also attached at the end of this document. In addition to these, the CD also includes softwares for participants, pictures and addresses of participants and other photos taken during the course.